Relationship of Interfaith in Tunisia (Critical Study of Ibn ‘Ashur Tafsir W.1973) - Amiur Nuruddin; Ahmad Qarib; Azwani Lubis; Muhammad Faisal Hamdani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
Relations between Muslims and non-Muslims will often experience disruption / friction if not addressed wisely, especially in terms of social politics, the order of social life. In Islam, Religion and Politics two things are difficult to separate. This often becomes a polemic to produce many interpretations and frictions in various regions and majority Muslim countries. Interpretation of the Qur'anic verses relating to religious and political relations also has a variety of colors and patterns which in the end can also produce identity theory in the practice of life. This paper aims to look at the opinion of Ibn Atsur in terms of the relationship / relationship between Islam and non-Islam, in what way and practice how Muslims and non-Muslims can work together and coexist and in terms of what and how they should be separated. Writing that uses this character qualitative method tries to look at the data based on Ibn Atsur's interpretation in his book "al-Tahr r wa al-Tanwir" and is combined with his political attitude described in his books and scientific books which tell him about him in facing the political situation in Tunisia. In interpreting the verses relating to interfaith relations, Ibn Atsur looks more broadly giving freedom to non-Muslims. For example in interpreting Qs. Al-Mumtahanah verse 8-9 he said the reason for the prohibition of doing good to non-Muslims was hostility and in conditions of war "Religion" not other than that. Reasons other than religion cannot be justified in not doing good to non-Muslims and may do good to non-Muslims in all forms of goodness that are related to muamalah and relations between people. Even in terms of this flexibility politics also caused Ibn Atsur to face mass slander by being considered a supporter of the invaders for supporting dual citizenship in Tunisia and not at all suspicious of the French-Catholic colonialism when he appointed him Shaykh al-Isla Christian development in Tunisa. In other cases, Ibn ‘Ashur also displays a different attitude with other interpreters. In an interpretation of QS. Al-Maidah: [54], he said that it was not permissible to appoint Christian and Jewish leaders because of their religious differences. He added that making Jews and Christians as leaders could cause someone to get out of Islam (apostasy). Even in his political stance, Ibn Atsur once said that non-Muslims should not be made members of Shura or Majilis (Parliament, a type of DPR-MPR) on the grounds that they would never think of the religious interests of Muslims. Thus Ibn Atsur has an ambiguous attitude and changes in interpretation and progressive attitude by some scientists call him seeing the situation and the condition of the people he faces (dialectic).